Information System Design of Sales Promotion and Production Inventory Management using Fifo Method - Putra, Tri Andi Eka; Tamara, Selvi Yona; Mayefis, Reska (Institute Of Advanced Knowledge and Science, 2024)
Toko Kerupuk Sanjai Bintang Baru This company produces and sells its products to consumers, but starting from production, production and sales inventory management still fully uses a manual system, starting from calculating production profits, production sales policies based on expiration dates, as well as the sales system. still conventional. The methods used in this research are interviews, observation, literature study, analysis, system design, testing, and implementation. From this research it is hoped that the information system created can provide convenience in the implementation of the Sanjai Bintang Baru Store will improve its production methods and sales promotion, so that collaboration with information system technology can help and provide benefits to the Sanjai Bintang Baru Store itself.